Public Policy and Public Service Management: A Bibliometric Mapping of Scientific Research and Emerging Trends - Mutia, Ulmi Sri (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study analyzes the intellectual structure and research evolution in the field of public policy and public service management through a bibliometric approach using data from Scopus between 2019 and 2025. VOSviewer was employed to visualize citation networks, keyword co-occurrence, and thematic developments. The results show a significant increase in publications focusing on governance innovation, digital public services, and citizen participation. The network visualization identifies three major clusters: governance reform, e-government implementation, and performance accountability. The overlay visualization illustrates a shift from traditional bureaucratic models (2019 - 2021) toward digital transformation and sustainable governance (2022 - 2025). The density visualization reveals the dominance of studies originating from Europe and Asia, reflecting global interest in adaptive governance. This research contributes to a deeper understanding of trends and collaboration patterns within the field, offering insights for scholars and policymakers to enhance the effectiveness and inclusivity of public service management.